2017
DOI: 10.1021/acsenergylett.6b00639
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Thermoelectric Figure of Merit and Enhanced Mechanical Stability of p-type AgSb1–xZnxTe2

Abstract: High-performance thermoelectric materials are desirable in the lower-medium temperature range (450–650 K) for low-grade waste heat recovery. We report a thermoelectric figure of merit (zT) of 1.9 at 585 K in p-type AgSb1–x Zn x Te2, which is the highest value measured among the p-type materials in the 450–650 K range. A high average thermoelectric figure of merit (zTavg) of 1.3 is achieved in AgSb0.96Zn0.04Te2. Moreover, the AgSb1–x Zn x Te2 sample exhibits a hardness value of ∼6.3 GPa (nanoindentation), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 58 publications
(104 reference statements)
3
97
0
Order By: Relevance
“…Slowly cooled alloys with x = 0.1 and x = 0.17 exhibit the highest TE performance, showing ZT values of 1.2 and 1.1 at 610 K, respectively. It is clear that high ZT values in Ag 1−x Sb 1+x Te 2+x alloys can also be obtained without extrinsic doping as reported previously [2][3][4][5][6]. All samples reveal lack of long-term stability, which causes degradation of the β phase and the TE performance, in agreement with the phase diagram of the Ag-Sb-Te system.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Slowly cooled alloys with x = 0.1 and x = 0.17 exhibit the highest TE performance, showing ZT values of 1.2 and 1.1 at 610 K, respectively. It is clear that high ZT values in Ag 1−x Sb 1+x Te 2+x alloys can also be obtained without extrinsic doping as reported previously [2][3][4][5][6]. All samples reveal lack of long-term stability, which causes degradation of the β phase and the TE performance, in agreement with the phase diagram of the Ag-Sb-Te system.…”
Section: Discussionsupporting
confidence: 83%
“…Numerous studies, concerning the TE performance of AgSbTe 2 -alloys with various dopants, reported very large values of TE figure of merit ZT > 1.3 [2][3][4][5][6]. That is mainly due to the extremely low thermal conductivity of the material in the range of 0.5-0.7 W·m −1 ·K −1 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With years of development, an extraordinary zT for AgSbTe 2 has been realized. [36,37,[46][47][48][49][50][51][52][53][54] It should be noted that stoichiometric AgSbTe 2 has been reported to be thermodynamically unstable, and partial decomposition into Ag 2 Te and Sb 2 Te 3 would be observed during thermal cycling. [55][56][57] Moreover, phase transition of Ag 2 Te at ≈418 K (if exist) leads to a detrimental effect on the stability of thermoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…There are several thermoelectric materials reported in the literature with ZT ∼ 1, such as AgSbTe 2 , PbTe, SnTe, SiGe, etc. Recently, there were some interesting reports where ZT > 1 was reported for similar compounds [6][7][8]. However, their applicability is not feasible till now due to various reasons, such as limited range of temperatures, difficulty in preparing materials in large quantities, toxicity of elements, degradation as a function of time or temperature, etc.…”
Section: Introductionmentioning
confidence: 99%